Living between margins: senses of being ribeirinho sertanejo in the Baixo São Francisco - Silva, Cícero Bezerra da; Vargas, Maria Augusta Mundim (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
The article presents the meanings of Ser Ribeirinho Sertanejo. This construction is due to the conviviality expressed in the relationship with the river and the backlands. We present as an empirical research reference the low course of the São Francisco River in the semiarid lands domain, between the states of Alagoas and Sergipe. In this investigative process, we used the semi-structured interview, seeking to involve the lands, waters and people that characterize and give uniqueness to a socioeconomic, cultural and identity environment marked by the profound interaction of man and nature. Aimed at the foundations of phenomenology, we seek to present the São Francisco River as a place and territory qualified by the experiences, daily practices and the relations of belonging that characterize the meanings of being-in-the-world and being a sertanejo riverine.